Superior performing nano‐enabled metal oxide varistors. Issue 3 (20th August 2019) - Tan, Daniel Q.
Abstract: Commercial metal oxide varistor devices are subject to nonuniformity, defects and coarse grain size, low working voltage, high leakage current, and mechanical cracking issues. This work tempted to make use of nanopowders and alternative sintering processes to achieve uniform microstructure and superior varistor performance. These nano‐enabled compositions exhibit lower sintering temperatures (650‐1050°C), smaller grain sizes (0.5‐2 μm), enhanced nonlinear coefficient (30‐130) in DC I‐V characteristics, higher varistor voltages (240‐2500 V/mm), and low leakage current (<1 μA/cm 2 ). Conventional sintering offers highest nonlinearity. Spark plasma sintering and microwave sintering techniques show advantages in reducing grain sizes and sintering temperatures. Spark plasma sintering is particularly effective in achieving better varistor performance for the nano‐enabled MOV compositions after a post‐SPS sintering for sufficient oxygen diffusion. Microwave sintering needs higher sintering temperatures and additional research for the nano‐enabled MOV compositions to offer equivalent electrical properties. Abstract : SPS/annealing process of nano‐enabled MOV compositions resulted in submicron grain sizes (<1.0 µm), lower sintering temperature (<750°C), and higher varistor voltage (2 kV/mm). Conventional sintering process gives rise to higher nonlinearity (>60) and lower leakage current (<10‐7 A/cm 2 ). Microwave sintering did not deliver equally good varistor performance.